Analysis of Legal Liability in Force Majeure Arbitration Civil Matters Due to Decrease in Currency Value (Study of Decision Number 976 K/Pdt/2012) - Meisarah Tri Anjani; Dea Khairat; Wulan Dari; Mhd Ary Fadhillah Nasution; Lufti Sugara (ISNU Nine-Star Multidisciplinary Journal, 2024)
A currency downgrade refers to an economic downturn that has a significant impact on the economy of one or more countries, including inflation and international trade. This can affect business relationships. In some cases, a currency downgrade can lead to a default, and the party who suffered the loss can invoke force majeure. However, currency downgrades are not considered force majeure under Indonesian law. In the case of business disputes, arbitration is often a strong and final resolution mechanism, although the award can still be overturned if there is fraud or forged documents. Force majeure must be caused by an extraordinary event that cannot be foreseen, such as a natural disaster or social conflict. A valid sale and purchase agreement is legally binding on both parties, and breaches of the agreement can be resolved through the courts or arbitration. Dispute resolution through arbitration is seen as a faster and more flexible alternative to litigation in court.